2018
DOI: 10.12809/hkmj177173
|View full text |Cite
|
Sign up to set email alerts
|

Mesh-related complications from reconstructive surgery for pelvic organ prolapse in Chinese patients in Hong Kong

Abstract: The rates of mesh exposure and re-operation were consistent with those reported in the literature, suggesting no significant differences in outcome between Chinese and Western patients for this type of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 25 publications
0
19
1
Order By: Relevance
“…Very‐low‐quality evidence in both RCT and NRSI studies suggests that women who underwent SC suffered a lower rate of mesh complications than women who underwent TVM surgery over a 1‐year period; however, no significant differences were found during the 1‐year follow up. In the RCT group, 18–22 the pooled odds ratio was 0.42 (95% CI 0.18–0.98; I 2 = 0%; P = 0.05), and eight NRSIs with a follow‐up duration of >1 year 23–25,28,31,32,37,38 yielded a pooled odds ratio of 0.38 (95% CI 0.34–0.43; I 2 = 0%; P < 0.01). Three other NRSIs 26,33,36 with follow‐up durations of <1 year presented no significant differences in the occurrence of complications, with a pooled odds ratio of 0.77 (95% CI 0.25–2.33; I 2 = 0%; P = 0.84) (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Very‐low‐quality evidence in both RCT and NRSI studies suggests that women who underwent SC suffered a lower rate of mesh complications than women who underwent TVM surgery over a 1‐year period; however, no significant differences were found during the 1‐year follow up. In the RCT group, 18–22 the pooled odds ratio was 0.42 (95% CI 0.18–0.98; I 2 = 0%; P = 0.05), and eight NRSIs with a follow‐up duration of >1 year 23–25,28,31,32,37,38 yielded a pooled odds ratio of 0.38 (95% CI 0.34–0.43; I 2 = 0%; P < 0.01). Three other NRSIs 26,33,36 with follow‐up durations of <1 year presented no significant differences in the occurrence of complications, with a pooled odds ratio of 0.77 (95% CI 0.25–2.33; I 2 = 0%; P = 0.84) (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…There were 20 eligible studies, including four RCTs [18][19][20][21][22] (there were two articles 20,21 about one RCT), four prospective studies [23][24][25][26] and 12 restrospective studies, [27][28][29][30][31][32][33][34][35][36][37][38] identified from the MEDLINE, EMBASE, Cochrane Library and clinicaltrials.gov databases. A PRISMA flow diagram depicting the study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature suggests a high recurrence rate with VH-PFR-M (15%) and VH-PFR-SSF (33%) [1]. Owing to recent U.S. Food and Drug Administration warnings about mesh-related complications, it is important to explore other techniques that would reduce both recurrence rate and complication rate [2].…”
Section: Introductionmentioning
confidence: 99%